Integrating STEAM via virtual reality: a TPACK-focused training model for pre-service secondary mathematics teachers using NeoTrie VR - Rodríguez, José L.; García López, María del Mar (Frontiers in Education, 2026)
IntroductionThis paper presents the findings from the second iteration of a study aimed at enhancing pre-service secondary math teachers’ competence in integrating immersive virtual reality (IVR) into 3D geometry education. The second iteration builds on the first cycle’s exploratory phase, addressing the need for more structured guidance and hands-on experience in using IVR for STEAM-focused teaching.MethodsThe study involved 33 pre-service teachers who participated in focused training sessions on NeoTrie VR, including collaborative design of teaching sequences, peer feedback, and a final presentation. The TPACK (Technological, Pedagogical, and Content Knowledge) framework was used to assess the participants’ development.ResultsThe analysis of the participants’ work revealed significant improvements, especially in the technological components of TPACK. A 15.5% increase in the average score of the final TPACK-based assignment was observed between the first and second cycles, indicating that the structured training led to a higher level of competence in using IVR for teaching.DiscussionThese findings highlight the importance of structured training in IVR for pre-service teachers. By overcoming initial technological barriers and building confidence, the training enabled teachers to effectively integrate NeoTrie VR into their future mathematics teaching, transforming traditional teaching and learning processes.